PENGARUH UKURAN AKUNTAN PUBLIK DAN AUDIT DELAY TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2018-2020 - DAVINA MARIANNE SUMARDI; LORIANA SIREGAR SUJIMAN (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study was conducted with the aim of analyzing the effect of the variables of Public Accounting Firm Size and Audit Delay on Auditor Switching. The data in this study uses secondary data in the form of audited annual financial reports from food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period by recording data accessed through the IDX official website. Based on predetermined criteria, the data obtained were 66 total samples consisting of 22 companies in 3-year financial statements. Data analysis in this study used descriptive statistics, multicollinearity test, overall model fit test, model feasibility test (hosmer and lemeshow’s goodness of fit), coefficient of determination (Nagelkerke r square), and logistic regression significance test. The results of this test show that (1) the size of the Public Accounting Firm has no effect on Auditor Switching, and (2) Audit Delay has no effect on Auditor Switching